ENVIRONMENTAL PROTECTION IN ARMED CONFLICT ACCORDING TO INTERNATIONAL HUMANITARIAN LAW - Aini, Desy Churul; Banjarani, Desia Rakhma (Tadulako Law Review, 2018)
The environment is a victim of various armed conflicts that occur in some parts of the world. Such as Congo war in 1998 that create environmental damage like deployment of the HIV-AIDS virus, the extinction of national parks, wildlife poaching and the forest burning. In addition the Rwanda civil war in 1994 affected the loss of biodiversity, natural resources and population decline in rare animals such as the African Gorillas. While the former Yugoslavia war in 1991 that impact in environmental pollution of water, air and land that threaten human survival.The environment becomes a victim when the war was happend its caused the human, but on the other side, the environment can’t be separated from human life because somehow humans need the environment to. However, when the war was happend human can’t maintaining the environment even though there have been rules that regulate about the protection of the environment when the war takes place. Therefore, its necessary to analysed an environmental protection in armed conflict according to international humanitarian law.This research is discusses about how an environmental protection in armed conflict according to international humanitarian law, which aims to explain the regulations that apply to protect the environment at the armed conflict. This research uses normative law approach (literature research).The results of this study show that environmental protection in armed conflict is regulated in the conventions of international humanitarian law both from the Hague Law and the Geneva Law. In The Hague law the environmental protection is governed by the IV Hague Convention 1907of respecting the laws and customs of war and land Art 23 (g) and Art 55. In the Geneva Law an environmental protection is contained in the IV Geneva Convention 1949 Art 53 and Additional Protocol I in 1977 Art 35 (3), 54, 55, 56, 59, and Art 68. Basically both of Geneva and Hague Law against the use of weapons during the war that have an effected in environmental damage and the existence of precautions in the war on environmental protection life. Beside the Geneva and the Hague Law there are have other arrangements to protect the environment in the event of a war that is in ENMOD Convention Art 1 and 2.